2018
DOI: 10.1371/journal.pone.0193031
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses retinal angiogenesis and inflammation in vitro and in vivo

Abstract: The oral anti-diabetic drug metformin has been found to reduce cardiovascular complications independent of glycemic control in diabetic patients. However, its role in diabetic retinal microvascular complications is not clear. This study is to investigate the effects of metformin on retinal vascular endothelium and its possible mechanisms, regarding two major pathogenic features of diabetic retinopathy: angiogenesis and inflammation. In human retinal vascular endothelial cell culture, metformin inhibited variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 53 publications
2
76
0
Order By: Relevance
“…our observation, that need to be con rmed on larger numbers, seems to support the idea that an early use of metformin might protect the eye, likely because it does not induce hypoglycaemia, detrimental toward the retina [30], or -alternatively -by exerting endothelial protection [31].…”
Section: Discussionsupporting
confidence: 74%
“…our observation, that need to be con rmed on larger numbers, seems to support the idea that an early use of metformin might protect the eye, likely because it does not induce hypoglycaemia, detrimental toward the retina [30], or -alternatively -by exerting endothelial protection [31].…”
Section: Discussionsupporting
confidence: 74%
“…Experiments in endothelial cells and STZ-induced diabetes mice by us and others also identified significant attenuation of ICAM-1 and MCP-1 levels, as well as inflammatory responses by metformin [28, 29]. The antiangiogenic activity of metformin was demonstrated in various endothelial cell lines as well as retinal neovascularization mouse models [29, 30]. …”
Section: Discussionmentioning
confidence: 98%
“…However, AMPK may not account for all actions of metformin, as demonstrated by the preserved metabolic effect of metformin in liver-specific AMPK-deficient mice [32]. The regulation on endothelial inflammatory and angiogenic responses by metformin also has been shown through both AMPK-dependent and AMPK-independent mechanisms [29, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Han et al [37] in their in vitro study found that metformin directly inhibits angiogenesis of human retinal vascular endothelial cells (hRVECs) and has prevented tumor necrosis factor alpha (TNFα)-induced upregulation of multiple inflammatory cytokines in hRVECs.…”
Section: Protective Effect On Diabetic Retinopathymentioning
confidence: 99%
“…AMPK activation was suggested to be protective for the tissues that are undergoing metabolic stress. However, the regulation on endothelial inflammatory and angiogenic responses by metformin also has been shown through both AMPK-dependent and AMPK-independent mechanisms [37,40].…”
Section: Protective Effect On Diabetic Retinopathymentioning
confidence: 99%